The influence of dispersing and stabilizing of indium tin oxide nanoparticles upon the characteristic properties of thin films - Peukert, Wolfgang; Reindl, Armin; Mahajeri, Mahdi; Hanft, J (Thin Solid Films, 2009)
Stable suspensions of indium tin oxide nanoparticles were prepared by dispersing for 1 h in ethanol and stabilizing with 2-[2-(2-Methoxyethoxy)ethoxy]acetic acid. Particle size, morphology, and structure were characterized by a combination of dynamic light scattering, high resolution transmission electron microscopy, and X-ray diffraction. Spin coating of the stable suspensions resulted in densely packed films with a high transparency. Dispersing times exceeding 1 h led to a significant "overdispersing" effect, i.e. an increasing aggregate size of the suspensions was observed. Zeta-potential, pH, and X-ray photoelectron spectroscopy measurements were conducted to achieve a detailed understanding of the effect of "overdispersing". With an increasing time of dispersion, i.e. with a decreasing stability of the suspensions, the thin films fabricated by spin coating displayed an increasing pore size distribution and surface roughness. In addition a strong decrease in transmittance and in conductivity was observed. © 2008 Elsevier B.V. All rights reserved.
Keywords: Conductivity; Dispersion; Indium tin oxide; ITO; Morphology; Nanoparticles; Stability; Thin films; Transmittance